Acylated Ghrelin as a Multi-Targeted Therapy for Alzheimer's and Parkinson's Disease - Reich, Niklas; Hölscher, Christian (Frontiers in Neuroscience, 2020)
Much thought has been given to the impact of Amyloid Beta, Tau and Alpha-Synuclein in the development of Alzheimer’s disease (AD) and Parkinson’s disease (PD), yet the clinical failures of the recent decades indicate that there are further pathological mechanisms at work. Indeed, besides amyloids, AD and PD are characterized by the culminative interplay of oxidative stress, mitochondrial dysfunction and hyperfission, defective autophagy and mitophagy, systemic inflammation, BBB and vascular damage, demyelination, cerebral insulin resistance, the loss of dopamine production in PD, impaired neurogenesis and, of course, widespread axonal, synaptic and neuronal degeneration that leads to cognitive and motor impediments. Interestingly, the acylated form of the hormone ghrelin has shown the potential to ameliorate the latter pathologic changes, although some studies indicate a few complications that need to be considered in the long-term administration of the hormone. Given its impressive multi-talented nature, this review will illustrate the potent neuroprotective properties and critically evaluate the therapeutic benefits of acylated ghrelin for the treatment of AD and PD.